Carya aquatica, Water Hickory - Michael G. Andreu; Melissa H. Friedman; Mary McKenzie; Heather V. Quintana; Robert J. Northrop (EDIS)
FOR 267, a 2-page fact sheet by Michael G. Andreu, Melissa H. Friedman, Mary McKenzie, Heather V. Quintana, and Robert J. Northrop, describes this native deciduous tree found in wet but well-drained soils along stream banks and flood plains, ranging from the eastern Carolinas, south to central Florida, and west to Eastern Texas – scientific and common names, description, allergen, and applications. Includes references. Published by the UF School of Forest Resources and Conservation, June 2010.